2018
DOI: 10.1177/1557988318774243
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Reporting of Intimate Partner Violence Among Male Couples in Three U.S. Cities

Abstract: Intimate partner violence (IPV) is a prevalent and pressing public health concern that affects people of all gender and sexual identities. Though studies have identified that male couples may experience IPV at rates as high as or higher than women in heterosexual partnerships, the body of literature addressing this population is still nascent. This study recruited 160 male–male couples in Atlanta, Boston, and Chicago to independently complete individual surveys measuring demographic information, partner violen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 38 publications
1
25
1
3
Order By: Relevance
“…Ahora bien, la naturaleza transversal de las pesquisas pudo haberse debido a la dificultad de acceso a esta población; entre otras razones, por la estigmatización del fenómeno dentro de la propia comunidad LGBT (Barrientos et al, 2016). Por otra parte, se observó un incremento en el estudio de los aspectos asociados a la violencia, especialmente en el análisis de los factores que contribuyen a su presencia; en ese sentido, destacaron el abuso de sustancias, la discriminación homofóbica, la homofobia internalizada y el diagnóstico de VIH (Craft & Serovich, 2005;Davis et al, 2016;Duncan et al, 2018;Finneran et al, 2012;Finneran & Stephenson, 2014a, 2014bGreenwood et al, 2002;Oliffe et al, 2014;Semple et al, 2017;Stephenson & Finneran, 2017a;Suárez et al, 2018;Téllez & Walters, 2011;Woodyatt & Stephenson, 2016).…”
Section: Discusión Y Conclusionesunclassified
See 2 more Smart Citations
“…Ahora bien, la naturaleza transversal de las pesquisas pudo haberse debido a la dificultad de acceso a esta población; entre otras razones, por la estigmatización del fenómeno dentro de la propia comunidad LGBT (Barrientos et al, 2016). Por otra parte, se observó un incremento en el estudio de los aspectos asociados a la violencia, especialmente en el análisis de los factores que contribuyen a su presencia; en ese sentido, destacaron el abuso de sustancias, la discriminación homofóbica, la homofobia internalizada y el diagnóstico de VIH (Craft & Serovich, 2005;Davis et al, 2016;Duncan et al, 2018;Finneran et al, 2012;Finneran & Stephenson, 2014a, 2014bGreenwood et al, 2002;Oliffe et al, 2014;Semple et al, 2017;Stephenson & Finneran, 2017a;Suárez et al, 2018;Téllez & Walters, 2011;Woodyatt & Stephenson, 2016).…”
Section: Discusión Y Conclusionesunclassified
“…Dentro de las limitaciones de los estudios revisados, es preciso señalar que en algunos artículos el uso del término HSH incluyó únicamente a hombres gays o bisexua-les (Suárez et al, 2018), aunque también se utilizó como referente de hombres que no se identifican con ninguna de estas orientaciones (Duncan et al, 2018); esto es importante, pues puede inducir a confusiones en el uso de los términos, pero también en las interpretaciones derivadas de los datos obtenidos.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Within this class of variables (i.e., SSIPV-specific risk factors), internalized homonegativity, which refers to negative affect and attitudes directed toward the self and one’s personal sexual orientation ( Meyer, 1995 , 2003 ), seem to take a main role in predicting IPV perpetration among sexual minorities. Several studies identified a positive association between levels of internalized homonegativity and SSIPV perpetration ( Balsam and Szymanski, 2005 ; Edwards and Sylaska, 2013 ; Suarez et al, 2018 ; Miltz et al, 2019 ). As reported by authors ( Byrne, 1996 ; Cruz and Firestone, 1998 ; Bartholomew et al, 2008 ) and drawing from a psychodynamic conception of violence ( Glasser, 1998 ; Fonagy, 1999 ; Asen and Fonagy, 2017 ; Yakeley, 2018 ), the internalization of the sexual stigma can entail a negative representation of the self and negative affect (e.g., shame, humiliation) which are experienced as unbearable and psychically threatening by the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Intimate partner violence (IPV), including emotional, physical, or sexual violence, is a pervasive and devastating problem that can affect people across any gender identity or sexual orientation (Suarez et al, 2018). Although most scholarship, to date, has explored IPV exposure among cisgender (nontransgender), heterosexual females (Finneran, & Stephenson, 2013; Kubicek, McNeeley, & Collins, 2015), mounting evidence suggests that LGBTQ individuals are at equal or even greater risk of IPV exposure relative to cisgender, heterosexual individuals (Dank, Lachman, Zweig, & Yahner, 2014; Edwards, Sylaska, & Neal, 2015; Stotzer, 2009).…”
Section: Introductionmentioning
confidence: 99%